The teaching of Xitsonga poetry to secondary school learners in Mhala, Mpumalange Province with reference to a sample of poems from the anthologies of Masebenza B.J., Chauke S.P. and Magaisa J.M. - Mona, Mulaleni Jacob (My University, 1997)
Refer to the document
Thesis (M.Ed.) -- University of the North, 1997
Keywords: Tsonga language; Tsonga language -- Study and teaching (Elementary) -- South Africa; Tsonga poetry